Frontline Science: Cytokine‐mediated developmental phenotype of mouse eosinophils: IL‐5‐associated expression of the Ly6G/Gr1 surface Ag. Issue 3 (1st November 2019) - Limkar, Ajinkya R.; Mai, Eric; Sek, Albert C.; Percopo, Caroline M.; Rosenberg, Helene F.
Abstract: Eosinophils have broad and extensive immunomodulatory capacity; recent studies have focused on the roles of distinct eosinophil subsets in specific tissue microenvironments. Ly6G is a GPI‐linked leukocyte surface Ag understood primarily as a marker of mouse neutrophils, although its full function is not known. Here, we show that Ly6G/Gr1, detected by mAbs 1A8 (anti‐Ly6G) and RB6‐8C5 (anti‐Gr1), is detected prominently on a significant fraction of eosinophils from mouse bone marrow and bone marrow‐derived culture, with fractions expressing this Ag increasing in IL‐5‐enriched microenvironments. Among our findings, we identified SiglecF + Gr1 + eosinophils in bone marrow from naïve, allergen‐challenged and IL‐5 transgenic mice; SiglecF + Gr1 + eosinophils were also prominent ex vivo in bone marrow‐derived eosinophils (bmEos) in IL‐5‐enriched culture. Reducing the IL‐5 concentration 20‐fold had no impact on the rate of generation of SiglecF + bmEos but did result in a marked increase in the Gr1 − fraction (from 17.4 ± 2% to 30 ± 2.3%, *** P  < 0.005). Reducing the IL‐5 concentration also enhanced chemotaxis; SiglecF + Gr1 − bmEos were considerably more responsive to eotaxin‐1 than were their SiglecF + Gr1 + counterparts. These results suggest that (i) IL‐5 regulates the expression of Ly6G/Gr1, either directly or indirectly, in cells of the eosinophil lineage, (ii) eosinophils generated in response to high concentrations of IL‐5 can be distinguished from those generated under homeostatic conditions by expression of the Ly6G/Gr1 cell surface Ag, and (iii) expression of Ly6G/Gr1 may have an impact on function, directly or indirectly, including the potential to undergo chemotaxis in response to eotaxin‐1. Abstract : The neutrophil leukocyte antigen Ly6G is expressed prominently on mouse eosinophils in bone marrow in association with increasing concentrations of the eosinophil‐active cytokine, interleukin‐5.